Estimation of coupling loss factors for rectangular plates with different materials and junctions. (October 2019) - Bhagwan, Mandale Maruti; Popuri, Bangarubabu
In statistical energy analysis, coupling loss factor is the essential parameter for vibro-acoustic analysis of complicated structures. The coupling loss factors have been estimated using energy-level difference method. The tightening torque applied at structural junction has been varied. Higher values of coupling loss factor have been observed for higher tightening torque on bolted junction. The coupling loss factors have been determined for various structural junctions of rectangular composite plates. The riveted and bolted junctions have been examined for composite plates in same plane and size. The coupling loss factors for bolted junction are relatively higher than that for riveted junction of composite plates. The values of coupling loss factors are found to increase with increasing tightening torque applied at structural junctions of composite plates. It is also noted that the experimental results of coupling loss factors for point junctions vary with changes in fiber orientations of composite plates. It is firmly believed that the various findings of the coupling loss factors in this article help for vibro-acoustic analysis of complicated structures.